Italian Mediterranean Policy and Russia Between â€œRisorgimentoâ€ and the â€œGreat Warâ€ - Battaglia, Antonello (Richtmann Publishing, 2011)
The Mediterranean has been an area of great importance for Italian and Russian foreign policies. The great Tsarist empire,although being landlocked, has always shown great interest for the Mediterranean Sea. In particular the Tsarist policy has been directedtoward the strategic Straits of Bosphorus and Dardanelles, whose eventual conquest would have allowed the introduction into theMediterranean routes. This policy was due to the lack of ports on